Pemasaran Produk Lokal Berbasis Kesehatan sebagai Strategi Peningkatan Kesejahteraan Masyarakat Desa Plenen sebagai Desa Penyangga Kawasan Industri Terpadu Batang - Ainun Ganisia; Karmanis Karmanis; Sugiyanto Sugiyanto (Public Service and Governance Journal, 2026)
This study aims to analyze the marketing of health-based local products in Plenen Village as a buffer village of the Batang Integrated Industrial Estate and its implications for community welfare. The identified problems include limited human resource capacity, restricted market access, and limited understanding of modern marketing strategies among micro and small business actors. This study employs a descriptive qualitative approach with a case study design. Primary data were obtained through in-depth interviews and field observations, while secondary data were collected from official documents, development reports, and related publications. Data analysis techniques included data reduction, data presentation, and drawing conclusions using source and method triangulation to ensure validity. The results indicate that the people of Plenen Village have diverse potential in health-based local products, including healthy processed foods and herbal products. The marketing strategies applied include direct marketing, digital marketing, and partnerships with local communities, which significantly improve community income and welfare. Major challenges still include limited product innovation and human resource capacity. This study concludes that marketing health-based local products can be an effective strategy to enhance the welfare of buffer village communities around industrial estates, provided it is supported by empowerment, innovation, and adequate policies.